Stargardt disease: clinical features, molecular genetics, animal models and therapeutic options. Issue 1 (4th August 2016) - Tanna, Preena; Strauss, Rupert W; Fujinami, Kaoru; Michaelides, Michel
Abstract : Stargardt disease (STGD1; MIM 248200) is the most prevalent inherited macular dystrophy and is associated with disease-causing sequence variants in the gene ABCA4 . Significant advances have been made over the last 10 years in our understanding of both the clinical and molecular features of STGD1, and also the underlying pathophysiology, which has culminated in ongoing and planned human clinical trials of novel therapies. The aims of this review are to describe the detailed phenotypic and genotypic characteristics of the disease, conventional and novel imaging findings, current knowledge of animal models and pathogenesis, and the multiple avenues of intervention being explored.